Effectiveness to the reversal of the burden proof system in handling corruption case - Deddy Mursanto; La Ode Muhammad Karim; Mashendra Mashendra (Jurnal Hukum Volkgeist, 2020)
Corruption is an act that can harm State finances and cause losses to the people's economy. This study aims to determine the arrangement of the burden of proof reversals system of corruption according to the applicable provisions and the proper regulation in implementing the system of reversing the burden of proof to be done optimally. This study uses a normative juridical research methodology with a statute approach. This research's data analysis method is descriptive qualitative by describing the problems and facts in writing from the literature. The study indicates that the burden of proof reversal system concerning the Eradication of Corruption Crimes contained in Law no. 20 of 2001 is limited only to the offense of gratification regulated in Article 12 B paragraph (1) letter a. The withdrawal presumption proof can also be extended to the defendant's property, which is claimed to be connected to the accused's case (Article 37 A) and the property of the defendant (who has not been charged) which is not accused of corruption as a result of a criminal act (Article 38 B). Reversal of the burden of proof in the law of corruption is a reversal of the burden of proof impartial public prosecutor and the defendant alike must prove but / the same element proved different.